Plasmacytoid dendritic cell sensing of hepatitis E virus is shaped by both viral and host factors - Joshi, Garima; Décembre, Elodie; Brocard, Jacques; Montpellier, Claire; Ferrié, Martin; Allatif, Omran; Mehnert, Ann-Kathrin; Pons, Johann; Galiana, Delphine; Dao Thi, Viet Loan; Jouvenet, Nolwenn; Cocquerel, Laurence; et al. (Life science alliance, 2025)
Type I and III interferons critically protect the host against viral infection. Previous studies showed that IFN responses are suppressed in cells infected by hepatitis E virus (HEV). Here, we studied the anti-HEV function of IFN secreted by plasmacytoid dendritic cells (pDCs), specialized producers of IFNs. We showed that pDCs co-cultured with HEV-replicating cells secreted IFN in a cell contact-dependent manner. This pDC response required the endosomal nucleic acid sensor TLR7 and adhesion molecules. IFNs secreted by pDCs reduced viral spread. Intriguingly, ORF2, the capsid protein of HEV, can be produced in various forms by the infected cells, and we wanted to study their role in anti-HEV immune response. During infection, a fraction of ORF2 localizes into the nucleus, and glycosylated forms of ORF2 are massively secreted by infected cells. We showed that glycosylated ORF2 potentiates the recognition of infected cells by pDCs, by regulating cell contacts. On the other hand, nuclear ORF2 triggers immune response by IRF3 activation. Together, our results suggest that pDCs may be essential to control HEV replication.
Online veröffentlicht: 2. April 2025
Gesehen am 07.10.2025